Neurovascular examination : the rapid evaluation of stroke patients using ultrasound waveform interpretation - Alexandrov, Andrei V. (Chichester, West Sussex : Wiley-Blackwell, 2013)
The use of neurovascular ultrasound is of increasing importance in neurological practice, both for radiologists and increasingly by neurologists themselves. Written by the world's most renowned expert, this book explainsultrasound examination of a stroke patient scanning protocols interpretation of the results Case examples (with a standard template presentation correlating presentation to waveform output) reinforce the book's practical nature. Illustrated with photos of the tests, explanations, and with actual waveforms, images, and resu.
Understanding the mechanisms and dynamics of cerebrovascular events -- Time is brain and brain is flow! -- The power of observation -- Applied principles of ultrasound physics -- Applied principles of hemodynamics -- Real time ultrasound measures -- Emergent examination -- Diagnostic waveforms and algorithms -- Differential diagnosis -- Integration of information and case-based problem solving.
Includes bibliographical references and index.
Print version record.
Keywords: Cerebrovascular disease -- Diagnosis; Cerebrovascular disease -- Ultrasonic imaging; Stroke -- ultrasonography; Stroke -- diagnosis; MEDICAL -- Neurology; Cerebrovascular disease -- Diagnosis; Cerebrovascular disease -- Ultrasonic imaging; Electronic books